Synthesis of novel five-membered endocyclic sulfoximines — 1-aryl-3-(arylimino)-3, 5-dihydro-1, 4, 2-dithiazole 1-oxides. Issue 30 (27th July 2017) - Hua, Yong; Zhang, Wenjie; Wang, Xin; Ge, Zemei; Li, Runtao
Abstract: A novel kind of five-membered endocyclic sulfoximines, 1-aryl-3-(arylimino)-3, 5-dihydro-1, 4, 2- dithiazole 1-oxides, were synthesized through addition/cyclization of chloromethyl aryl sulfoximines with aryl isothiocyanates under mild reaction conditions in moderate to good yields. Graphical abstract: